Measurement report: Aircraft observations of aerosol and microphysical quantities of stratocumulus in autumn over Guangxi Province, China – daylight variation, vertical distribution, and aerosol–cloud interactions - S. Liu; H. Wang; D. Zhao; D. Zhao; W. Zhou; Y. Du; Z. Zhang; P. Cheng; T. Zhao; Y. Ke; Z. Wu; M. Huang (Atmospheric Chemistry and Physics)
Aerosols and clouds play essential roles in the global climate system, and aerosol–cloud interactions have a significant impact on the radiation balance, water cycle, and energy cycle of the Earth–atmosphere system. To understand the effect of aerosols on the vertical distribution of stratocumulus microphysical quantities in southwest China, we analyzed data from nine aircraft observations over Guangxi from 10 October to 3 November 2020. This analysis focused on the daylight variation characteristics and formation mechanisms of stratocumulus microphysical profiles, considering the influence of aerosol number concentration in relation to the source of air mass and individual cases. Aerosol number concentration (Na) and cloud droplet concentration (Nc) decreased gradually with an altitude increase below 1500 m and did not change with a height between 1500 and 3300 m. The temperature inversion layer at the top of the planetary boundary layer (PBL) hindered the increase in the cloud droplet particle size. The lower layer of the stratocumulus cloud in Guangxi mainly contained small-sized cloud droplets (effective diameter of a cloud droplet (Ed) < 15 µm), and the middle and upper layers of cloud droplets were large-particle-size cloud droplets (Ed > 20 µm). The vertical distribution of cloud microphysical quantity had apparent daylight variation. When aerosols in the PBL were transported to the upper air (14:00 to 20:00 Beijing time, BJT), Nc in the lower layer decreased, and the small-particle-size cloud droplets (Ed < 20 µm) in the middle layer and upper layer increased. Aerosols from the free atmosphere were transported into the PBL (10:00 to 13:00 BJT), providing an abundance of cloud condensation nuclei, which increased the number of small-particle-size cloud droplets in the lower layer of the cloud (near the top of the PBL). The characteristics of cloud microphysical quantities (Nc and Ed) were also affected by the source of air mass and the height of the PBL. Na and Nc were high under the influence of land air mass or aerosols within the PBL, and the cloud droplet number concentration spectrum was unimodal. Na and Nc were low under the influence of marine air mass or above the boundary layer, and the cloud droplet number concentration spectrum was bimodal. The relationship between stratocumulus and aerosol in this region is consistent with the Twomey effect. Ed and Na remain negatively correlated in different liquid water content ranges, and the FIE (aerosol first indirect effect) ranged from −0.07 to −0.58.